Prediction of typhoon design wind speed with cholesky decomposition method. (24th March 2018) - Huang, W.F.; Sun, J.P.
Summary: Typhoon simulation method that integrates typhoon wind field model, probability distributions of typhoon key parameters, and Monte Carlo simulation method has long been used to predict typhoon design wind speeds of structures. In the research, the empirical typhoon wind field model with a novel parameter B model of Holland's radial pressure profile is first introduced and validated with typhoon Hagupit's simulation. The results show that relatively good typhoons can be simulated with this empirical typhoon wind field model. Then, the cholesky decomposition method used in typhoon simulation method is proposed that allows achieving all correlated typhoon key parameters simultaneously. Finally, the cholesky decomposition method is used to generating typhoon key parameters in Hong Kong, and typhoon design wind speeds for different return periods are predicted with typhoon simulation method. In addition, typhoon design wind speeds derived from historical typhoon key parameters and typhoon key parameters generated without considering cholesky decomposition method are also predicted, respectively. The predicted typhoon design wind speeds are compared and the results demonstrate that the cholesky decomposition method should be incorporated into typhoon simulation method.